2015
DOI: 10.1063/1.4936184
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic (MHD) flow analysis of second grade fluids in a porous medium with prescribed vorticity

Abstract: Steady and unsteady flow of a second grade MHD fluid in a porous medium with Hall current effects is studied. Assuming an à priori known vorticity proportional to the stream function up to an additive uniform stream, exact solutions for velocity field are obtained corresponding to different choices of pertinent flow parameters. Graphical results are presented to depict the influence of pertinent flow parameters on the considered MHD flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
0
11
0
Order By: Relevance
“…In another study, the authors Rasool et al [20] use the famous SPECTRAL method to figure out the impact of EMHD by a vertical Riga plate in a second-grade type nanofluid. Akbar et al [21] numerically investigated the MHD flow of second-grade fluids in a porous medium with prescribed vorticity. Aurangzaib et al [22] reported the unsteady MHD type mixed convective flow based on a micropolar porous surface.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the authors Rasool et al [20] use the famous SPECTRAL method to figure out the impact of EMHD by a vertical Riga plate in a second-grade type nanofluid. Akbar et al [21] numerically investigated the MHD flow of second-grade fluids in a porous medium with prescribed vorticity. Aurangzaib et al [22] reported the unsteady MHD type mixed convective flow based on a micropolar porous surface.…”
Section: Introductionmentioning
confidence: 99%
“…Ishak et al [27] examined two-dimensional MHD stagnation point flow towards stretching sheet with variable surface temperature. Akbar et al [28] have analyzed the MHD flow of viscoelastic fluids taking a porous medium. e study of MHD free convection flow of viscoelastic fluid through a porous wedge has been studied by Rashidi et al [29].…”
Section: Introductionmentioning
confidence: 99%
“…Abd‐Alla et al 16 have considered the peristaltic stream of a Jeffrey liquid under the impact of a radially fluctuating attractive field in a cylinder with an endoscope. Akbar et al 17 have explored the MHD stream investigation of second‐grade liquids in a permeable medium with the recommended vorticity.…”
Section: Introductionmentioning
confidence: 99%